Issues in Software Development in Composition - Barker, Thomas T. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
Noting the increase in the number of teachers developing computer software for composition instruction, this paper explores the issues that are shaping the direction of computer assistance in writing instruction. The first half of the paper deals with specific questions teachers must consider as they design software. These are divided into categories for (1) design, including the pedagogical theory underlying the software, the audience and focus of the software, and professional standards; (2) development, including hiring good programers at competitive wages, management strategies, and testing and quality assurance standards; and (3) distribution, including copyright, licensing, distribution methods, and packaging. The second half of the paper explores the broader issues confronting teachers developing software for composition instruction. These include the environment or conditions under which the software will be used, the role that teachers will play in that environment, and the characteristics of software programing as it is likely to be practiced by English teachers. (HTH)
ERIC Note: Paper presented at the Meeting of the UCLA Conference on "Computers and Writing: New Directions in Teaching and Research" (Los Angeles, CA, May 4-5, 1985).
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Assisted Instruction; Computer Software; Educational Innovation; Educational Media; Higher Education; Instructional Materials; Programing; Secondary Education; Teaching Methods; Writing Instruction; English Teachers; Opinion Papers; Speeches/Meeting Papers